Synthesis of BODIPY-pyrrolo[3,4-b]pyridin-5-ones via Ugi-Zhu/cascade reactions and studies of fluorescence response toward viscosity - Flores-Reyes, Julio C.; Galano, Annia; Rojas-Montoya, Sandra M.; Blancarte-Carrazco, Luis; Xochitiotzi-Flores, Elba; García-Ortega, Héctor; Farfán, Norberto; Islas-Jácome, Alejandro; González-Zamora, Eduardo (Frontiers in Chemistry, 2024)
A series of seven new meso-phenyl pyridin-5-one conjugates were synthesized in one experimental step by using a Sc(III)-catalyzed Ugi-Zhu three-component reaction coupled to a cascade sequence (aza Diels-Alder / N-acylation / aromatization) as post-MCR functionalization process. Further experimental studies were performed behind understanding the fluorescence response toward viscosity. All compounds exhibited a linear response between increasing viscosity (DMSO and glycerol mixtures) and fluorescence intensity. The different substituents also influenced the photophysical properties. Furthermore, in DMSO all compounds exhibited dual emission. Each band is attributed to the pyrrolo [3,4-b]pyridin-5-one and BODIPY moieties, respectively. The electronic structure of all compounds was computed by DFT and TD-DFT calculations, allowing to determine the molecular orbitals involved in the electronic transitions.